Investigating the Role and Position of Multiple Personality Components on the Organizational Commitments of Senior Financial Managers in Companies Listed on the Tehran Stock Exchange - Zeinab Alizadeh Someeh; Marzieh Ebrahimi Shaghaghi; Hossein Eslami Mofid Abadi (راهبرد مدیریت مالی)
Senior managers play an essential role in organizations. They shape organizational strategy and culture, define missions including opportunities for new markets, and business models. Their commitment to the organization is critical to organizational performance, but research on the personality traits of top managers and their commitment to organizations is limited.Therefore, this research has been conducted with the aim of the role and position of multiple personality components in fulfilling the organizational obligations of senior financial managers in companies listed on the Tehran Stock Exchange. Where relying on self-affirmation theory, the implications of the "dark triad traits" of top managers (narcissism, psychopathy, and Machiavellianism) for their organizational commitment and the mediating role of role clarity and the moderating role of resource availability are examined. In this regard, In this research, the three-component conceptual model developed by Allen and Mayer (1990) has been used to distinguish affective, continuance and normative commitment. A research model was developed from the literature review and the three-component model developed by Allen and Mayer, and then it was developed using the structural equation method on a sample of 384 respondents from all activists, brokers, investors, experts. Seniors and specialists of the companies admitted to the Tehran Stock Exchange were evaluated. The results of this study show that psychosis has a significant effect on organizational normative commitment, narcissism an organizational normative commitment, and Machiavellian personality approach on emotional organizational commitment in companies listed to the Tehran Stock Exchange. Also, the availability of resources as a moderating variable has a significant effect on the relationship between multiple personality components of senior financial managers and organizational commitments in companies listed on the stock exchange. Finally, the results showed that the multiple personality components of senior financial managers have a significant effect on the transparency of the role in the companies.